2009
DOI: 10.1167/iovs.08-2812
|View full text |Cite
|
Sign up to set email alerts
|

Control of Patterns of Corneal Innervation by Pax6

Abstract: Pax6 dosage nonautonomously controls robust directed radial projection of corneal neurons, and the guidance cues for growth cone guidance are not solely dependent on directed epithelial migration. There is little evidence that ARK represents neurotrophic keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 51 publications
6
24
0
Order By: Relevance
“…At approximately 3 weeks after birth, the subbasal nerves orient toward the central cornea, which results in a swirl pattern that persists during postnatal development and adulthood. 68,69 A similar swirl pattern was observed in human. 70 Although studies have shown radial projections of stromal nerves in the adult human cornea similar to chick, their patterning during development remains unclear.…”
Section: Corneal Innervationsupporting
confidence: 76%
“…At approximately 3 weeks after birth, the subbasal nerves orient toward the central cornea, which results in a swirl pattern that persists during postnatal development and adulthood. 68,69 A similar swirl pattern was observed in human. 70 Although studies have shown radial projections of stromal nerves in the adult human cornea similar to chick, their patterning during development remains unclear.…”
Section: Corneal Innervationsupporting
confidence: 76%
“…38,40 In mouse models, heterozygous Pax6 +/-adult mice exhibited decreased epithelial innervation and nerve patterns were disrupted. 41 In humans, IVCM has been used to quantify subbasal epithelial nerves in LSCD, where a markedly reduced nerve density has likewise been found in a case series without aniridia patients 35 and in a series including two aniridia patients. 34 In a Swedish cohort of 16 aniridia subjects where IVCM was used, a wide range of subbasal nerve density was reported, including 3 patients with abnormally high innervation of the central cornea.…”
Section: Corneal Nervesmentioning
confidence: 99%
“…VEGF is also known to influence nerve growth [10;11] which may be a contributing factor to PAX6 since the dosage of PAX6 itself is the main factor contributing to pathological pattern of corneal innervation in aniridia [12]. It has also been suggested [13] that nerve growth factor receptor TrkA is involved in the regulation of the normal stem cell turnover.…”
Section: Introductionmentioning
confidence: 99%